Improving the Capacity of Physics Teachers in the Development of Laboratory Experiment Kits Based on Video Analysis and Modeling Tool - Mairizwan, Mairizwan; Kamus, Zulhendri; Asrizal, Asrizal; Yohandri, Yohandri (PILLAR OF PHYSICS EDUCATION, 2023)
Science subjects really need a learning model that makes students learn a lot from experience, not from verbal speeches and memorizing concepts given by the teacher. Experience can only be gained through practical activities and experiments which can ultimately improve students' science process skills. The reality in the field shows that physics experimental activities cannot be carried out optimally because a lot of equipment cannot be operated, the number of experimental sets is not enough and the equipment needed is quite expensive. The aim of this research is to increase teachers' skills in developing low-cost laboratory experimental kits by combining technology from video analysis and modeling tools with the research object being the physics MGMP teachers of Agam district. Implementation stages include providing training/workshops, practical implementation and evaluation of results. After carrying out this activity stage, the results obtained are video analysis products from participants and student worksheets. The results of this research can be analyzed and concluded that physics teachers' understanding and skills in carrying out video-based practical activities have increased due to limited practical equipment in the laboratory. The increase in participants' understanding can be seen from the results and their satisfaction with the implementation of laboratory experiment kit development activities based on video analysis and modeling tools. Therefore, improving these skills has a very good impact on teachers to increase learning variations that attract students' interest, and assist students in understanding Physics concepts correctly and being able to find their best potential